Morphology of Chok Anan mango flower grown in Malaysia - Ding, Phebe; Darduri, Khairul Bariah (Academic Journals, 2013)
A fundamental understanding of mango flowering in the tropics is essential to efficiently utilize cropping management systems which could extend both the flowering and crop production seasons. However, the information and appreciation of the floral biology of this popular fruit species is still lacking. Therefore, the objective of this work was to observe the morphology of Chok Anan mango flowers using scanning electron microscope. The Chok Anan mango flower is monoecius where both the male and hermaphrodite flowers exist in the same panicle. The fruit develops from the hermaphrodite flower while the male flower contributes the pollen when pollination occurred. The Chok Anan mango flowers contained five sepals and five petals arranged in a whorl. There were not much differences in the structure of sepals and petals between the male and hermaphrodite flowers. The structure of the petals is not flat but billowy. Both sepals and petals consist of ground parenchyma tissue with laticifer and idioblast cells, starch granules and vascular bundle tissues. Trichomes are present in both sepals and petals. The male flower has the same structure as the hermaphrodite flower except that it does not have carpel. Further study is needed to understand the peculiarities of the floral morphology to allow us to predict mango production.